Reinterpretasi Makna ‘Uqud Sebagai Perjanjian Pranikah Perspektif Qiraah Mubadalah: (Kajian QS. Al-Maidah Ayat 1) - Faishal Al Ghifari; Fajar Bakti; Eni Zulaiha (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
Prenuptial agreement is a concept, which has not been widely discussed by Muslim scholars, especially in the field of Quran and tafsir. Gender-biased interpretations of verses about prenuptial agreements can erode the role of the prenuptial agreement. Therefore, this study seeks to identify the usual interpretation of gender, and gender-fair interpretation of the Quranic verse related to prenuptial agreements. This research uses qualitative research methods, with descriptive-analysis techniques. The data collection is done with a literature study approach. Based on the assessment conducted, the following are the results of the research. First, Buya Hamka's interpretation of QS. Al-Maidah verse 1, is included in the category of gender-biased interpretation. This can be seen from his interpretation has a tendency towards one party. Second, feminist or gender-fair interpretation of QS. Al-Maidah verse 1, is more oriented towards more equitable values, especially in the cross-gender sphere. This is shown through the implementation of the principle of mufa'alah in the preparation of a prenuptial agreement. In addition, the points in the contents of the prenuptial agreement, generally correlate with the principle of al-Kuliyyah al-Khamsa in maqashid ash-shar'iyyah Ash-syatibiy. One example, the requirement regarding the separation of property falls into the category of hifdz al-Maal.